2011
DOI: 10.1089/acm.2009.0559
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis on Symptoms and Signs of Chronic Low-Back Pain Based on Traditional Chinese Medicine Theory

Abstract: Four (4) TCM major groups of pathophysiology could explain 37% of variance of 31 symptoms and signs of the CLBP patients. Thirteen (13) items are not groupable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…From TCM point of view, Xiong et al used factor analysis to explore patterns of symptoms and signs from patients with chronic low-back pain based on the TCM theory. They found that four factors were extracted from LBP patients, including (1) Qi and/or blood stagnation, (2) cold/damp, (3) a part of “kidney deficiency,” and (4) warm/heat [23]. The research of Sherman et al also showed that Qi and blood stagnation or Qi stagnation was found for 85% of LBP patients and kidney deficiency was found for 33–51% of LBP patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…From TCM point of view, Xiong et al used factor analysis to explore patterns of symptoms and signs from patients with chronic low-back pain based on the TCM theory. They found that four factors were extracted from LBP patients, including (1) Qi and/or blood stagnation, (2) cold/damp, (3) a part of “kidney deficiency,” and (4) warm/heat [23]. The research of Sherman et al also showed that Qi and blood stagnation or Qi stagnation was found for 85% of LBP patients and kidney deficiency was found for 33–51% of LBP patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…TCM believes that low back pain has a close relationship with the imbalance of qi and blood, meridians, and visceral functions. Limb swelling and pain may occur, as a consequence of poor circulation of qi and blood, qi stagnation, and meridian blockage [ 19 ]. Qi stagnation and blood stasis, meridian obstruction, and meridian malnutrition may lead to low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with spleen-qi deficiency often have decreased immunity, manifested by vague pain below xyphoid which can be relieved by pressing and warming [31], anorexia, nausea, vomiting, diarrhea, and pale faces and lips [32]. Such symptoms as tiredness, fatigue, loose stool, and poor appetite are significantly correlated to cancer [33].…”
Section: Differentiation From Liver Cancer With Other Zheng Classificmentioning
confidence: 99%